Bioinformatics Storing Databases - Abed, Raghad; Al-Najjar, Yusra (Technium BioChemMed, 2021)
An exceptional branch of data that requires huge databases has been shown lately from genome sequencing projects which is a field that employs computational approaches to answer biological questions. With this huge sequence of information that is available for researchers, bioinformatics plays a big role in studying basic medical-biological problems. The challenge that faces bioinformatical scientists is to help in discovering genes and designing molecular models, site-directed mutagenesis, and other experiments that reveal the unknown relationships concerning the structure and function of genes and proteins. This become a big challenge especially with the huge amount of data that is generated using the human genome and other systematic sequencing efforts up till now. Bioinformatics solves biological problems depending on available data. It is concerned with creating databases and predicting the outcome of lab experiments.